Diagnosis of Zinner syndrome: A case of rare occurrence - Nguyen Duy Thinh; Vu Duy Lam; Nguyen Thi Le My; Le Thanh Dung; Nguyen Dinh The; Tran Quang Loc (Radiology Case Reports, 2025)
Zinner syndrome is a rare congenital urinary condition, secondary to disruptions in the embryonic development process between the fourth and 13th week of pregnancy, particularly due to abnormalities in the development of the distal mesonephric duct. It is characterized by the triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ipsilateral vas deferens obstruction. We present a case of a young male patient who came to the hospital for a health check-up. A computer tomography scan revealed the absence of the right kidney, dilated vas deferens, and a right seminal vesicle cyst. The patient was advised that there was no indication for surgical intervention and recommended to follow up and monitor the condition after a period of time for re-evaluation.